Indonesia’s Economic Growth And Its Impact On The Formal Sector Workforce - Balkis, Azzahra; Ruhaedi, Rudi; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
Indonesia’s post-reform economic growth has had a significant impact on the structure of the formal sector workforce, with increased participation of young workers and women. This study aims to analyze the relationship between economic growth and the demographics of the formal sector workforce, as well as the challenges that arise, such as gender gaps, skills mismatches, and inequality in access to education. The method used is demographic analysis, which analyzes secondary data from the Central Bureau of Statistics (BPS) and other related sources, to map the composition of the workforce by age, gender, and education level. The results show that despite progress in the participation of women and young workers, gender gaps in wages and employment opportunities are still significant, while young workers face challenges with skills that do not match market needs. In addition, although the level of formal sector education has increased, access to education in rural areas remains an obstacle. In conclusion, more inclusive policies, such as increasing access to education and skills training, and reducing gender gaps, are essential to ensure sustainable and equitable economic growth for all levels of society.